Sistem Informasi Penjadwalan Otomatis Media Sosial Instagram Untuk Mendukung Promosi Program Studi Di Universitas Dharma Andalas - Faradika Faradika; Renita Astri; Zulfahmi Zulfahmi (Prodi Sistem Informasi Universitas Dharma Andalas, 2020)
Instagram's social media automatic scheduling system is one of the innovations in the field of promotion to introduce study programs to many people through social media. With this scheduling application, it will be easy for the university to schedule content to be published on Instagram social media. This application works on the desktop made with the PHP programming language with MySQL database support. This research was conducted to obtain data directly from the Social Media Manager of the Study Program by conducting observations and direct interviews to the management team and related parties so that the data contained in this report is real. The system testing that is carried out is how the application works as a whole, namely where the system can send scheduling automatically to Instagram which is contained in the database, there is an input update from a user (in this case a lecturer user) through the existing application.